Lifelong Learning for Poverty Eradication - Raditloaneng, Wapula N.; Chawawa, Morgen (Springer International Publishing : Imprint: Springer, 2015)
This book illustrates the meaning and scope of lifelong learning and different types of poverty reduction programs prevalent generally in the African context and particularly in selected communities in Botswana. Lifelong learning is important for all stakeholders in poverty reduction to develop a better understanding of the scope and extent of poverty so that they can make informed decisions on best ways of tackling poverty. The book succinctly showcases community development and engagement initiatives and experiences from selected African universities and how the interaction of the universities and their respective communities resulted in a major transformation in the lives of poor families through exposure to some engagement strategies that effectively gave them a better future in their fight against poverty. This book develops in the reader a better understanding of the dynamics and dilemma of poverty and its negative effects on individuals and communities. But it answers the plight of the poor by equipping them with effective and practical tools to transform their lives and take full control of their destiny. ·         Provides a conceptual understanding of lifelong learning ·         Describes practical aspects and indicators of poverty and how it requires tackling through a multi-sectoral approach ·         Focuses on poverty reduction in all fronts, including development of an entrepreneurship mind-set.